O CURRÍCULO E O PERFIL DO EGRESSO DE UM CURSO DE LICENCIATURA EM QUÍMICA SOB A PERSPECTIVA DISCENTE. - ALMEIDA, Anderson Nogueira (2018)
Much is discussed about the need for more efficient policies of initial teacher training through the social importance of the teacher profession. For this, theories are consolidated, guidelines are reformulated, however, the feeling of devaluation, stagnation and regression still persist. One reflection of this panorama is the lack of interest in the teaching career, in which the number of undergraduate students in the Natural Sciences areas seems to be insufficient to meet the demand of the Brazilian educational system. It is necessary to recognize that there are formative failures. Thus, we seek with this work to understand more closely the initial teacher training (in specific of Chemistry of the Federal University of Maranhão / UFMA), from the perspective of the future / new teacher. What professional course is Chemistry Degree from UFMA forming? Are there weaknesses in the training process? If so, what are they? These are important questions to understand the progress of the educational system and to see possible educational improvements at the local and national levels. In order to do so, we have studied the curriculum of the Chemistry Degree of the Federal University of Maranhão: characterizing the purposes of the course in terms of the objectives and justification proposed, through a documentary study of the Political Project of the Course (PPC), before the theories and curricular guidelines; representing, among other aspects, the area of activity, the knowledge groups, the personal profile and the professional profile developed in the course. The study was carried out in the light of the Social Representation Theory (SRT) according to Serge Moscovici, through a systemic questionnaire of mixed character, with Analysis of Content according to Franco (2003) and Bardin (2011) for specific questions. Through the analysis we realize that the new egress is not leaving the course to act in Basic Education; was prepared predominantly by the area of the Technical and Conceptual Group of Chemistry, in which there is the massive preparation of conceptual chemical basis, leaving aside the development of skills of the pedagogical and humanistic groups; and has a predominantly traditional and reproductive profile. Thus, we have concluded that the undergraduate course in Chemistry of UFMA needs to consider in its curriculum factors linked to the critical and post-critical theories for an effective training of individuals in the area. The relations, comparisons and interpretations of this work collaborate for reflections about a curricular structure that is in conformity with the greater objective that the term "teacher training course" suggests, namely: turn into a teacher.